Photo inactivation of virus particles in microfluidic capillary systems. Issue 7 (3rd February 2016) - Ren, Yudan; Crump, Colin M.; Mackley, Malcolm M.; Li Puma, Gianluca; Reis, Nuno M.
ABSTRACT: It has long been established that UVC light is a very effective method for inactivating pathogens in a fluid, yet the application of UVC irradiation to modern biotechnological processes is limited by the intrinsic short penetration distance of UVC light in optically dense protein solutions. This experimental and numerical study establishes that irradiating a fluid flowing continuously in a microfluidic capillary system, in which the diameter of the capillary is tuned to the depth of penetration of UVC light, uniquely treats the whole volume of the fluid to UVC light, resulting in fast and effective inactivation of pathogens, with particular focus to virus particles. This was demonstrated by inactivating human herpes simplex virus type‐1 (HSV‐1, a large enveloped virus) on a dense 10% fetal calf serum solution in a range of fluoropolymer capillary systems, including a 0.75 mm and 1.50 mm internal diameter capillaries and a high‐throughput MicroCapillary Film with mean hydraulic diameter of 206 μm. Up to 99.96% of HSV‐1 virus particles were effectively inactivated with a mean exposure time of up to 10 s, with undetectable collateral damage to solution proteins. The kinetics of virus inactivation matched well the results from a new mathematical model that considers the parabolic flow profile in the capillaries, and showed the methodology is fully predictable and scalable and avoids both the side effect of UVC light to proteins and the dilution of the fluid in current tubular UVC inactivation systems. This is expected to speed up the industrial adoption of non‐invasive UVC virus inactivation in clinical biotechnology and biomanufacturing of therapeutic molecules. Biotechnol. Bioeng. 2016;113: 1481–1492. © 2015 Wiley Periodicals, Inc. Abstract : UVC virus inactivation in optically thick protein solutions is rapid, efficient, non‐invasive, and scalable based on fluoropolymer microfluidic capillary systems, as demonstrated by a new numerical model and experimental data with a large enveloped HSV‐1 virus particles.